1988
DOI: 10.1007/bf00263647
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical chemotherapy: Combination with dimethyl sulfoxide does not enhance cytotoxicity in vitro

Abstract: There is evidence that dimethyl sulfoxide (DMSO) can increase the anticancer activity of chemotherapeutic drugs. As DMSO is instilled into the bladder for interstitial cystitis, it could be readily adopted in clinical practice if it was found to enhance the effectiveness of the drugs used for intravesical chemotherapy. The purpose of this study was to investigate, using a human bladder cancer cell line, the hypothesis that DMSO enhances the activity of these agents. However, the addition of 4% DMSO to the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our observations in the present study are in concordance with those of previous studies, except for the MNU tumorogenesis achieved by Hashimato et al 7 Like Hashimato et al 7 we also used 50% DMSO as a standard dose that is widely in use for interstitial cystitis and achieved the expected results. Lower doses of DMSO, such as 4% DMSO used by Walker et al, 8 may not be enough to potentiate transmural uptake of chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our observations in the present study are in concordance with those of previous studies, except for the MNU tumorogenesis achieved by Hashimato et al 7 Like Hashimato et al 7 we also used 50% DMSO as a standard dose that is widely in use for interstitial cystitis and achieved the expected results. Lower doses of DMSO, such as 4% DMSO used by Walker et al, 8 may not be enough to potentiate transmural uptake of chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 98%
“…Attempts have been made to increase the efficacy and enhance antitumor activity of this treatment by promoting the penetration of drugs into urothelial cells by the addition of Tween 80, urokinase or dimethylsulfoxide (DMSO). [5][6][7][8] The aim of the present experimental study was to determine whether pretreatment with intravesical DMSO would modify the absorption of the instilled chemotherapeutic drug, both to the normal bladder mucosa and to tumoral lesions. group (n = 50), which received N-methyl-N-nitrosourea (MNU); (ii) the sham group (n = 5); and (iii) the control group (without previous MNU administration; n = 6).…”
Section: Introductionmentioning
confidence: 99%
“…Thirty or more years ago, DMSO (10–15%) was a promising new anti-cancer drug because it induced polymerization and stabilization of microtubules [6], which in turn it was believed, would inhibit mitosis and kill proliferating cancer cells. However, extensive studies of DMSO showed no anti-cancer properties [7], [8]. In fact, DMSO became an organic solvent for other chemotherapeutic drugs such as Taxol [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the in vitro sensitivities of human melanoma xenografts correlated strongly with in vivo response, except in two cases in which the derived cell lines also lost the capacity to produce tumours on transplantation (Tveit et al, 1981). Thirdly, we have shown that cell lines derived from a tumour type curable by chemotherapy, testicular germ cell tumours, are on average five times more sensitive to adriamycin and cis-platin than bladder cell lines (Walker et al, 1985). Cumulatively these studies suggest that, following careful characterization, cell lines that reflect the drug sensitivities of their tumour of origin can be selected.…”
mentioning
confidence: 75%